Biodiesel production from waste lignocellulosic materials using in-house oleaginous yeast - Chawla, Simarpreet Kaur (My University, 2015)
Oleaginous yeast strain Rhodotorula sp. DBTIOC-ML3, previously isolated from India marine biodiversity, was used in this study. Strain DBTIOC-ML3 can not only tolerate high concentration of inhibitors such as acetic acid, HMF and furfural but also produce high biomass containing significant amount of lipid, which underlines the robustness of this strain. Major aim of this study was to replace costly yeast extract with cost effective nitrogen sources. For which different inorganic and organic nitrogen source were tested. Spent yeast from ethanol fermentation was found viable option to replace yeast extract in the media. Autolysis of the spent yeast released significant amount of protein and other nutrients, which was subsequently used as nitrogen and nutrient source in combination with non-detoxified liquid hydrolysate (NDLH) of different biomass. Ability of this strain to utilize sugars from NDLH of different lignocellulosic biomass and nitrogen source from spent yeast makes it suitable candidate for lipid production, which can be subsequently used for biodiesel production. Fatty acid profile of this strain contains large amount of palmitic and oleic acid, which further underlines the potential of this strain for biodiesel production.
M.Sc-Biotechnology-Dissertation
Keywords: Biodiesel; lignocellulose; oleaginous yeast; lipid; biotechnology